Synergistic Application of Platelet-Rich Fibrin and 1% Alendronate in Periodontal Bone Regeneration: A Meta-Analysis. (18th August 2019) - Li, Feifei; Jiang, Peipei; Pan, Jinhai; Liu, Chengcheng; Zheng, Liwei
Abstract : Periodontal bone regeneration relies on coupled and cooperative bone formation and resorption. Accordingly a novel strategy on concurrent use of platelet-rich fibrin (PRF) (anabolic agent) and 1% alendronate (ALN) (anticatabolic agent) was proposed recently in regenerative periodontal treatment. It was supposed to enhance bone formation and reduce bone resorption simultaneously. However, there is a lack of evidence-based studies to answer whether this concurrent application was superior to single application until now. Besides, concerns on ALN lead to some reservation on this synergistic way. ALN may impair new bone formation and necrotize jaws. Thus, in order to compare the clinical efficacy between PRF plus 1%ALN and PRF alone on periodontal bone regeneration, we performed present systematic review and meta-analysis. Because it is the prerequisite for measuring the combined efficacy of PRF plus 1%ALN, firstly we evaluated the effectiveness of 1%ALN. Our data indicated that adjunctive 1%ALN was effective in promoting periodontal bone repair. Further, PRF plus 1%ALN showed a greater capacity for periodontal regeneration than PRF alone with statistical significance. The findings of this study revealed the promising prospects on synergistic application of bone anabolic agents (PRF) and antiresorption medications (1%ALN) in regenerative periodontal treatment.